CHO cells expressing the human P5-ATPase ATP13A2 are more sensitive to the toxic effects of herbicide Paraquat - de Tezanos Pinto, Felicitas (2012)
P-ATPases are membrane transporters energized by ATP. The subfamily of P5-ATPases is the least studied P-ATPases and the ion substrate specificity of the P5 subfamily is not known. Mutations of the human P5ATPase gene ATP13A2 has been shown to underlie a form of Parkinson disease (PD). We investigated the link between ATP13A2 and environmental factors related to PD development. Increasing concentrations of the synthetic polyamine analog paraquat induced a greater cytotoxic effect over CHO cells expressing ATP13A2. Paraquat-toxicity was associated with increased production of cellular reactive oxygen species and this increment was reversed by the natural polyamine spermidine. Acridine orange fluorescence intensity suggested that ATP13A2 induced the expansion of acidic vesicles that become more alkaline upon external addition of spermidine. Polyamine uptake is proposed to be initiated by a plasma membrane carrier followed by sequestration into acidic vesicles of the late endocytic compartment through an unidentified active mechanism; because ATP13A2 is located in lysosomes and late endosomes, our results open the possibility that ATP13A2 could be one of those active transporters capable of transporting polyamines like spermidine as well as its toxic analog paraquat.